POLITENESS OF WOMEN’S LANGUAGE (JOSEIGO) BY SHIN TANOKURA IN DRAMA SERIES OF OSHIN - Eko Kurniawan (Jurnal Japanedu: Pendidikan dan Pengajaran Bahasa Jepang, 2018)
This study aims to assess information about variety of women’s language by Shin Tanokura, women’s language that represent the principles of politeness and politeness scale in drama series of Oshin. Research based on theory of Kindaichi (1988) for variety of women’s language and theory of Leech (2011) for the principles of politeness and politeness scale. This is kind of qualitative research. The method used in this research is the descriptive analysis. Source of data in this study is drama series of Oshin. While the data in this study are uttarances containing women’s language, women’s language that represent the principles of politeness and politeness scale. Data collection technique which used is observing method.The results showed, variety of women’s language by Shin Tanokura in drama series of Oshin is based on the theory of Kindaichi (1988): 1) Goi level, consists of using shuujoshi (wa, kashira, mono dan no), kantanshi (maa dan ara), ninshoudaimeishi (atakushi, atashi dan anata), koshou (~san, ~sama dan anata), keigo (teineigo, kenjougo dan sonkeigo) dan wago (tsuite iku); 2) Tougo level, consists of using iikirenai hyougen dan kurikaeshi hyougen; 3) Danwa level, consists of using youkyuu hyougen, aizuchi dan aisatsu, kimari monku. The classifications above represented in six maxims of the principles of politeness, tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim and sympathy maxim. According on theory of Leech (2011), there are three politeness scales, 1) Profit and loss scale, 2) Indirect scale and 3) Which like scale. Then, three scale are linked to one another and implemented in women’s language by Shin Tanokura in drama series of Oshin, the result are profit on addressees-direct-high, profit on addressees-direct-medium, profit on addressees-direct-low, profit on addressees-indirect-medium, profit on addressees-indirect-low, profit on speaker, addressees-direct-low and profit on speaker, addressees-indirect-high.